Overview of Nursing Professional Development: Major Revisions in 2016. Issue 4 (July 2016) - N/A,
Abstract : The Nursing Professional Development: Scope and Standards of Practice, 3rd Edition, was recently published by the Association for Nursing Professional Development. This latest version is intended to guide current and future nursing professional development practice. This article describes the major revisions to the scope and standards, along with their driving forces.